2021
DOI: 10.1080/14767058.2021.1895738
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of G6PD deficiency in Iranian neonates with jaundice: a systematic review and meta-analysis

Abstract: Objectives: This systematic review and meta-analysis study aimed to estimate the overall prevalence of Glucose-6-phosphate dehydrogenase (G6PD) deficiency in neonates with jaundice who were admitted to hospitals in Iran. Materials and methods: In this systematic review and metaanalysis, we searched PubMed/Medline, Scopus, ISI Web of Sciences, and Iranian Local databases up to December 2019.We calculated Prevalence and 95% Confidence Interval (95% CI) of G6PD deficiency as summary measures. We conducted subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The overall prevalence of G6PD deficiency in Iranian newborns with jaundice is reported to be 7%. 28 Our results showed that although UDCA can be effective in reducing unconjugated hyperbilirubinemia, it may not be very useful for neonates with risk factors such as G6PD deficiency. One possible cause could be the jaundice mechanism in G6PD enzyme-deficient newborns.…”
Section: Discussionmentioning
confidence: 63%
“…The overall prevalence of G6PD deficiency in Iranian newborns with jaundice is reported to be 7%. 28 Our results showed that although UDCA can be effective in reducing unconjugated hyperbilirubinemia, it may not be very useful for neonates with risk factors such as G6PD deficiency. One possible cause could be the jaundice mechanism in G6PD enzyme-deficient newborns.…”
Section: Discussionmentioning
confidence: 63%
“…Our study found that the type and prevalence of neonatal diseases are closely related to gender, gestational age, patient sources, delivery methods, and birth weight. The prevalence of most diseases in males was higher than in females (22)(23)(24). The analysis indicated a statistically significant difference between the patient sources.…”
Section: Discussionmentioning
confidence: 82%
“…The results showed that the proportion of males and females in each gestational age group was similar in inborn/outborn newborns. It was worth noting that gender had significant effect on neonatal prevalence, with males had higher prevalence than females (22)(23)(24). This demonstrates that although males accounted for more resources, there was no gender bias in treatment and referral.…”
Section: Discussionmentioning
confidence: 88%
“…The general prevalence of G6PD was reported to be 7% in the Iranian newborn population (11) , as the rate for Indonesia (12) and Saudi Arabia (13) varied from 1.7% to 10.5%, respectively. Meanwhile, the prevalence rate of this deficiency was reported to be 22% in this study.…”
Section: Discussionmentioning
confidence: 99%